Small animal surgical emergencies - Aronson, Lillian R. (Hoboken, New Jersey John Wiley & Sons Ltd., 2015)
Small Animal Surgical Emergencies is a practical reference to soft tissue and orthopedic emergencies commonly encountered in small animal practice.

• Covers common soft tissue and orthopedic emergencies
• Provides step-by-step procedures for stabilizing and operating on the emergent patient
Includes index (pages 543-554).
Keywords: Veterinary surgical emergencies; Pets -- Surgery